Potential Challenges of Developing Large-Scale Computing Infrastructures over Distributed Clouds - Mirza Mohammed Akram Baig (Mathematical Statistician and Engineering Applications, 2022)
Distributed information management systems facilitate numerous network services. However, the growing size of its infrastructures makes it difficult for administrators to manage large-scale dynamic distributed systems in an efficient manner. Developing large-scale computing infrastructures over distributed clouds presents various challenges. The key challenges addressed in this paper include scalability, load balancing, cloud interoperability, network latency, and fault tolerance. Scalability challenges mostly develop due to the increased monitoring of data of different sizes. Load balancing challenges develop because of the difficulties involved in harmonizing the workload in a distributed cloud. Concerning cloud interoperability, the sustenance of operations becomes more and more challenging as technology advances. Cloud interoperability challenges identified include portability and mobility, cloud-service integration, security, privacy, and trust, along with management, monitoring, and audit. Network latency challenges arise from delays that happen because of the time taken to process data on a server and return results back to the client on the network. The effectiveness of network latency measures depends on two factors – latency and traffic load, along with latency standards. Fault tolerance also counted among the potential challenges of developing large scale computing infrastructures over distributed computing. Some of the main challenges to consider include heterogeneity and the deficiency in standards, need for automation, downtime in the clouds, Recovery Point Objective (RPO) and Recovery Time Objective (RTO) considerations, as well as workloads in the cloud. Preparing for and minimizing the likelihood of these challenges can boost the development of large-scale computing infrastructures over distributed clouds.